2019
DOI: 10.1097/01.ogx.0000579680.37770.00
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Prescription Opioid Use in Women With Endometriosis: Evaluating Prolonged Use, Daily Dose, and Concomitant Use With Benzodiazepines

Abstract: To examine opioid use, opioid prescribing patterns, and timing of the first opioid prescription in endometriosis patients compared with matched women in the control group without endometriosis. METHODS:We conducted a retrospective analysis of the Clinformatics Datamart database. Women diagnosed with endometriosis from January 2006 through December 2016 and aged 18-49 years were compared with women in the control group matched on age, region, race, insurance payer, and plan type. Key outcomes included: filled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…15,16 Compared with matched women without endometriosis, women with endometriosis have a greater risk to fill a prescription for an opioid (adjusted risk ratio (RR): 2.91) and for filling prescriptions for prolonged use, a higher dose, and/or a benzodiazepine. 15 Women with endometriosis also have a greater risk at chronic opioid use (adjusted RR: 2.11). 15,16 A 2019 retrospective analysis of opioid-using women with endometriosis found that the average (standard deviation, SD) number of opioid prescriptions received was 4.6 (6.7), average days supply was 61.1 (128.6) days, and 18.1% received ⩾90 days of opioids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Compared with matched women without endometriosis, women with endometriosis have a greater risk to fill a prescription for an opioid (adjusted risk ratio (RR): 2.91) and for filling prescriptions for prolonged use, a higher dose, and/or a benzodiazepine. 15 Women with endometriosis also have a greater risk at chronic opioid use (adjusted RR: 2.11). 15,16 A 2019 retrospective analysis of opioid-using women with endometriosis found that the average (standard deviation, SD) number of opioid prescriptions received was 4.6 (6.7), average days supply was 61.1 (128.6) days, and 18.1% received ⩾90 days of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…14 Women with endometriosis have a greater risk at receiving opioids. 15,16 Compared with matched women without endometriosis, women with endometriosis have a greater risk to fill a prescription for an opioid (adjusted risk ratio (RR): 2.91) and for filling prescriptions for prolonged use, a higher dose, and/or a benzodiazepine. 15 Women with endometriosis also have a greater risk at chronic opioid use (adjusted RR: 2.11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in administrative claims databases have demonstrated that more than half of women fill a prescription for opioids, primarily short-acting opioids, after receiving a diagnosis code for endometriosis. 7 Further, women with endometriosis are more likely to fill at least one prescription for opioids than women without endometriosis, to be prescribed opioids at higher doses, for a greater number of days and concomitantly with benzodiazepines for up to 90 days than women without endometriosis, 6 leading to greater healthcare utilization and costs. 8,9 The current study expands these findings by demonstrating that there is an elevated risk of chronic opioid use.…”
Section: Results In Contextmentioning
confidence: 99%
“…Recent studies have demonstrated that women with endometriosis were more likely to fill a prescription for opioids, take higher doses, for a longer time, and concomitantly with benzodiazepines than women without endometriosis. 6,7 Further, women prescribed opioids had significantly higher healthcare burden, resource utilization and costs compared to non-opioid users over 2 years. 8,9 However the risk of chronic opioid use has not been quantified.…”
Section: Introductionmentioning
confidence: 99%